Predicting intraprocedural rupture and thrombus formation during coiling of ruptured anterior communicating artery aneurysms. (5th April 2016) - Fan, Lianghao; Lin, Boli; Xu, Ting; Xia, Nengzhi; Shao, Xiaotong; Tan, Xianxi; Zhong, Ming; Yang, Yunjun; Zhao, Bing
Abstract : Background: Intraprocedural rupture and thrombus formation are serious complications during coiling of ruptured intracranial aneurysms, and they more often occur in patients with anterior communicating artery (ACoA) aneurysms. Objective: To identify independent predictors of intraprocedural rupture and thrombus formation during coiling of ruptured ACoA aneurysms. Methods: Between January 2008 and February 2015, 254 consecutive patients with 255 ACoA aneurysms were treated with coiling. We retrospectively reviewed intraoperative angiograms and medical records to identify intraprocedural rupture and thrombus formation, and re-measured aneurysm morphologies using CT angiography images. Multivariate logistic regression models were used to determine independent predictors of intraprocedural rupture and thrombus formation. Results: Of the 231 patients included, intraprocedural rupture occurred in 10 (4.3%) patients, and thrombus formation occurred in 15 (6.5%) patients. Patients with smaller aneurysms more often experienced intraprocedural rupture than those with larger aneurysms (3.5±1.3 mm vs 5.7±2.3 mm). Multivariate analysis showed that smaller ruptured aneurysms (p=0.003) were independently associated with intraprocedural rupture. The threshold of aneurysm size separating rupture and non-rupture groups was 3.5 mm. Multivariate analysis showed that a history of hypertension (p=0.033), aneurysm neck size (p=0.004), and parent vessel angle (p=0.023) were independent predictors of thrombus formation. The threshold of parent vessel angle separating thrombus and non-thrombus groups was 60.0°. Conclusions: Ruptured aneurysms <3.5 mm were associated with an increased risk of intraprocedural rupture, and parent vessel angle <60.0°, wider-neck aneurysms, and a history of hypertension were associated with increased risk of thrombus formation during coiling of ruptured ACoA aneurysms.